Legal Uncertainty of Pelindo’s Land Management Rights in Port Development: A Normative Analysis of Regulatory Conflict - Irene Eka Sihombing; Endang Pandamdari; I Gede Yudi Arsawan; Ignatius Pradipa Probondaru (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines legal issues concerning land control by State-Owned Enterprises (SOEs), particularly PT Pelabuhan Indonesia (Persero) (Pelindo), in port development and expansion. In practice, Pelindo frequently acquires land or conducts reclamation using its internal funds; however, the resulting land is often transferred to the Ministry of Transportation (MoT) as the holder of Land Management Rights (Hak Pengelolaan/HPL). This arrangement creates legal uncertainty for Pelindo in managing land assets and establishing business partnerships. The study aims to analyze the legal certainty of Pelindo’s rights over land utilized for port development. Using a normative juridical method, the study examines legislation governing land law, shipping, and state-owned enterprises. The findings indicate that, despite financing land acquisition independently, Pelindo faces uncertainty regarding its legal status over the acquired land. Based on Law Number 5 of 1960, Law Number 2 of 2012, Law Number 17 of 2008, and Government Regulation Number 18 of 2021, the party that acquires land and maintains a legal relationship with it should be entitled to the relevant land rights. Therefore, transferring such land to the MoT is not legally required unless acquisition is financed through the State Budget (APBN). The study recommends regulatory harmonization, granting HPL to Pelindo, and strengthening its legal position to ensure greater legal certainty.